(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
Background: Burn and wound infections are one of the most important problem in Iraq because my country’s vulnerability to terrorism, and the repeated explosions in most areas of it, most causing of these infections were fungi, viruses and both Gram negative bacteria and positive bacteria as Pseudomonas aeruginosa and Staphylococcus aureus which form biofilm that causing multiple resistance drug for this bacteria. Methods: Forty clinical samples (24 wounds and 16 burns) were collected as wound and burn swabs from patients suffering from different types of wounds and burns patients who attending Medical City at a period between (November 2015 to January 2016). Culturing all swabs on MacConkey agar and Blood agar also used differential selective media as (Pseudomonas agar for Pseudomonas aeruginosa and Mannitol salt agar for Staphylococcus aureus). As well as used Vitek system for diagnosis and identificated bacteria. Results : This is the first study on sodium deoxycholate as antibiofilm and antibacterial activity against the bacteria (P. aeruginosa and S. aureus ) , where the results of the study showed sodium deoxycholate inhibits P. aeruginosa in both concentration 10-2 and 0.5 × 10-3 M. ,whilst its inhibit growth of S. aureus at a concentration higher than 1.0 × 10-4 M. Conclude: Staph. aureus is more sensitive to sodium deoxycholate than P. aeruginosa